Dynamic thermo-physical characteristics of high temperature gaseous hydrocarbon fuel thermal power generation for regeneratively cooled hypersonic propulsion system. (15th November 2020) - Xu, Qing; Li, Haowei; Feng, Yaoxun; Li, Xiaoning; Ling, Changming; Zhou, Chaoying; Qin, Jiang
Abstract: Power generation is urgent needed by the hypersonic air-breathing propulsion system, but the on-board power generation method is heavily restricted by its special structure. The outlet high temperature hydrocarbon fuel of the cooling channel in the hypersonic propulsion system can be used to generate power. However, the hydrocarbon fuel temperature is highly related with hypersonic propulsion system dynamic working conditions. To analyze the dynamic thermos-physical characteristics of high temperature hydrocarbon fuel thermal power generation (TPG) system, a zero-dimensional dynamic analytical model was developed, dynamic characteristics of the TPG system under different working conditions were conducted. Results show that there is overshoot of outlet fuel temperature under flight Mach number increase conditions and fuel equivalence ratio decrease conditions, which can be more than 10 K. Whilst there are both negative and positive overshoot of the generated power under the above working conditions, the largest magnitude of negative and positive overshoot can be more than 1 kW. Furthermore, the dynamic time of outlet fuel temperature and generated power are about 20–30s. Such complexity of dynamic characteristics brings difficulties in fuel supply for the propulsion system. Highlights: Model of the hydrocarbon fuel TPG system considering thermal-mechanical coupling effect was developed. Dynamic characteristics under Mach number and fuel equivalence ratio step change off-design condition was discussed. Fuel mass flow control strategy under Mach number and fuel equivalence ratio off-design condition was discussed.